Silver Nanoparticles and Polyphenol Inclusion Compounds Composites for Phytophthora cinnamomi Mycelial Growth Inhibition - Petruta Mihaela Matei; Jesús Martín-Gil; Beatrice Michaela Iacomi; Eduardo Pérez-Lebeña; María Teresa Barrio-Arredondo; Pablo Martín-Ramos (MDPI AG, 2018)
Phytophthora cinnamomi, responsible for “root rot” or “dieback” plant disease, causes a significant amount of economic and environmental impact. In this work, the fungicide action of nanocomposites based on silver nanoparticles and polyphenol inclusion compounds, which feature enhanced bioavailability and water solubility, was assayed for the control of this soil-borne water mold. Inclusion compounds were prepared by an aqueous two-phase system separation method through extraction, either in an hydroalcoholic solution with chitosan oligomers (COS) or in a choline chloride:urea:glycerol deep eutectic solvent (DES). The new inclusion compounds were synthesized from stevioside and various polyphenols (gallic acid, silymarin, ferulic acid and curcumin), in a [6:1] ratio in the COS medium and in a [3:1] ratio in the DES medium, respectively. Their in vitro response against Phytophthora cinnamomi isolate MYC43 (at concentrations of 125, 250 and 500 µg·mL−1) was tested, which found a significant mycelial growth inhibition, particularly high for the composites prepared using DES. Therefore, these nanocomposites hold promise as an alternative to fosetyl-Al and metalaxyl conventional systemic fungicides.